The role of biases in the judgement processing of (un)attractive faces in body dysmorphic symptomatology. (September 2021) - Dondzilo, Laura; Dietel, Fanny Alexandra; Buhlmann, Ulrike; MacLeod, Colin
Abstract: The current study tested the novel hypothesis that elevated facial appearance concern reflects a heightened tendency to judge facial appearance in terms of attractiveness, rather than in terms of attractiveness-irrelevant dimensions. Seventy-three females, reporting either high or low facial appearance concerns, were exposed to an individualised stimulus development protocol which involved a photoshoot and the subsequent selection of photographs perceived to be most and least attractive. Participants were then required to judge photographs in terms of either attractiveness or the eye gaze direction of the individual in the photograph. Results revealed that when judging attractiveness, low facial concern participants were faster to classify photographs as belonging to the attractive category rather than the unattractive category. We termed this potentially protective bias the General Attractiveness Recognition Advantage. Moreover, regardless of judgement required, high facial concern participants were faster to make responses to unattractive relative to attractive photographs of themselves. We termed this potential vulnerability bias the Efficient Processing of Unattractive Self. Further analyses revealed that the former bias associated with broader body dysmorphic symptomatology. The current findings, although inconsistent with the hypothesis under test, were novel in revealing two distinct mechanisms which distinguished high and low facial appearance concern individuals. Highlights: We investigated judgement processing biases in body dysmorphic symptomatology. Two distinct biases were found to differentiate high and low facial concern groups. The Efficient Processing of Unattractive Self is a potential vulnerability bias. The General Attractiveness Recognition Advantage is a potential protective bias. The latter bias was associated with broader body dysmorphic symptomatology.